Carbon Nanotube Composites for Electronic Packaging Applications: A Review - Lavanya Aryasomayajula; Klaus-Juergen Wolter (Journal of Nanotechnology)
Composite engineering comprises of metal matrix composites. They have high strength-weight ratio, better stiffness, economical production, and ease of availability of raw materials. The discovery of carbon nanotubes has opened new possibilities to face challenges better. Carbon Nanotubes are known for their high mechanical strength, excellent thermal and electrical properties. Recent research has made progress in fabricating carbon nanotube metal matrix and polymer-based composites. The methods of fabrication of these composites, their properties and possible applications restricted to the field of electronic packaging have been discussed in this paper. Experimental and theoretical calculations have shown improved mechanical and physical properties like tensile stress, toughness, and improved electrical and thermal properties. They have also demonstrated the ease of production of the composites and their adaptability as one can tailor their properties as per the requirement. This paper reviews work reported on fabricating and characterizing carbon- nanotube-based metal matrix and polymer composites. The focus of this paper is mainly to review the importance of these composites in the field of electronics packaging.